Tanggung Jawab Sosial Pemimpin Dalam Al-Qur’an - M Khalyl Fadhlan Darwis; Mayang Putri; Zaitun Ul Husna (Fakultas Ushuluddin dan Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2023)
In the era of globalization, the social responsibility of leadership is increasingly crucial. Every country and organization has a role in building a just and sustainable society. A leader in Islam must be fair, avoid injustice, and set a good example in all things. However, in reality there are still many leaders who are unjust towards their people, so that they do not carry out their social responsibilities as they should. This research uses a library research basis with qualitative methods, namely analyzing interpretive texts and library studies. The findings in this research are regarding social responsibility and its arguments, forms of social responsibility of leaders and criticism if it is not carried out.